Infection of genetically immunodeficient mice with Rickettia conorii - Montenegro, N. R.; Walker, D. H.; Hegarty, B. C. (My University, 1984)
In order to determine the definitive importance of T- and B-lymphocytes in immunity to Rickettsia conorii, mice genetically deficient in T-cells. B-cells, or both T- and B-cells were infected experimentally. T-lymphocytes rather than humoral antibodies were crucial to rikettsial clearance and a reduced mortality rate. Mice incapable of an antibody response to polysaccharide capsular antigens effectively controlled rickettsial infection with no mortality. In contrast, nude mice produced antibody to thymus-independent antigens early in the course of infection, yet experienced severe rickettsial infection resulting in death. The observed hepatic lesions are similar to those of boutonneuse fever. This model offers the opportunity to investigate rickettsial immune mechanisms and hepatic injury.